Molecular Epidemiology of Methicillin-Susceptible and Methicillin-Resistant Staphylococcus aureus in Wild, Captive and Laboratory Rats: Effect of Habitat on the Nasal S. aureus Population - Raafat, Dina; Mrochen, Daniel M; Al'Sholui, Fawaz; Heuser, Elisa; Ryll, René; Pritchett-Corning, Kathleen R; Jacob, Jens; Walther, Bernd; Matuschka, Franz-Rainer; Richter, Dania; Westerhüs, Uta; Pikula, Jiri; et al. (Toxins, 2020)
Rats are a reservoir of human- and livestock-associated methicillin-resistant Staphylococcus aureus (MRSA). However, the composition of the natural S. aureus population in wild and laboratory rats is largely unknown. Here, 144 nasal S. aureus isolates from free-living wild rats, captive wild rats and laboratory rats were genotyped and profiled for antibiotic resistances and human-specific virulence genes. The nasal S. aureus carriage rate was higher among wild rats (23.4%) than laboratory rats (12.3%). Free-living wild rats were primarily colonized with isolates of clonal complex (CC) 49 and CC130 and maintained these strains even in husbandry. Moreover, upon livestock contact, CC398 isolates were acquired. In contrast, laboratory rats were colonized with many different S.aureus lineages-many of which are commonly found in humans. Five captive wild rats were colonized with CC398-MRSA. Moreover, a single CC30-MRSA and two CC130-MRSA were detected in free-living or captive wild rats. Rat-derived S. aureus isolates rarely harbored the phage-carried immune evasion gene cluster or superantigen genes, suggesting long-term adaptation to their host. Taken together, our study revealed a natural S. aureus population in wild rats, as well as a colonization pressure on wild and laboratory rats by exposure to livestock- and human-associated S.aureus, respectively.
Keywords: laboratory; molekulární epidemiologie; Virulence Factors; Animals, Wild; clonal complex; Methicillin; Anti-Bacterial Agents; ekosystém; potkani Sprague-Dawley; Česká republika; host adaptation; Staphylococcal Infections; epidemiology; Německo; stafylokokové infekce; Czech Republic; habitat; coagulation; Staphylococcus aureus; immune evasion cluster; rat; divoká zvířata; nos; livestock; Nose; zvířata; Molecular Epidemiology; Germany; antibakteriální látky; Blood Coagulation; Rats, Sprague-Dawley; faktory virulence; Ecosystem; hemokoagulace; methicilin; Animals